Strong-field photoionization in two-center atomic systems - Fedyk, Jacqueline; Voitkiv, Alexander B.; Müller, Carsten (Physical review, 2018)
Photoionization of an atom A by a strong laser field in the presence of a spatially well-separated neighboring atom B is considered. The laser field frequency is assumed to lie below the ionization potential of atom A and be resonant with a dipole-allowed transition in atom B. In this situation, the ionization may occur either directly by multiphoton absorption from the laser field at the first atomic center or via an indirect pathway involving twocenter electron-electron correlations, where the neighbor atom B is first photoexcited and, afterwards, transfers its energy upon deexcitation radiationlessly to atom A. Considering monochromatic as well as bichromatic laser fields, we study various coupling regimes of the photoionization process and identify experimentally accessible parameter domains where the two-center channel is dominant.
Gesehen am 28.04.2020